Negligence in medical tourism: reforming the law / Khadijah Wahab - Wahab, Khadijah (2015)
Medical tourism has been on the rise with the number of medical tourists increasing globally. Malaysia has a great potential of becoming the hubs of medical tourism industry. The potential issues will arise on medical negligence. In law, medical tourists have to adhere the legal System in Malaysia. In case of claims made by medical tourist, the claims must be established according to Malaysia medical standards of practice and medical negligence laws in Malaysia. The Private Healthcare Facilities and Services Act (Act 586) 1998 and its Regulation’s 2006, medical Act 1971 and guidelines of Malaysia Medical Council do not provide sufficient procedures in regard to handling medical negligence case. This research may also made referral on New Zealand and Belgium in respect on handling compensation for the medical negligence cases. The structural interviews were carried out to find out the current methods on handling medical negligence that have been implemented by selected private hospitals in Malacca. Based on the research, it will benefit especially the Ministry of Health, the Malaysian Medical Council and medical practitioners in handling medical negligence with specifies provision for foreign medical tourist stipulate under the Private Healthcare Facilities and Services Act 1998. Finally, the research recommendation on the reforming a current laws in Malaysia in regards of medical negligence as an initiative to develop medical tourism performance in Malaysia.